ERK, p38 AND NF-kappaB SIGNALING IN MONOCYTE DERIVED DENDRITIC CELLS IN PATIENTS WITH MYELODYSPLASTIC SYNDROME. - Ilina Micheva; Liana Gercheva; Panos Ziros; Nicholas Zoumbos (Peytchinski Publishing, 2014)
We have previously demonstrated that in patients with myelodysplastic syndrome (MDS) monocyte-derived DCs (MoDC) exhibit some phenotypic and functional abnormalities. However, the mechanisms underlying the defective response have not yet been clarified. Aim: In the present study three different signaling pathways, ERK, p38K and NF-κB, were studied on MoDC from patients with MDS. Materials and methods: 7 patients with MDS and 5 healthy controls were included in the study. MACS separated CD14 cells were cultured for DC generation and further stimulated with TNF-α and LPS. A migration assay and ELISA were performed for the analysis of migration and IL-12p70 secretion. Western blot analysis was used for the detection of the phosphorylated forms of ERK and p38K. NF-κB binding activity was evaluated by electrophoretic mobility shift assay (EMSA). Results: In 6/7 patients the NF-κB binding activity in TNF-α and LPS stimulated MoDCs was lower compared to controls. This was accompanied by lower migratory capacity and IL-12p70 secretion. TNF-α and LPS induced phosphorylation of p38 and ERK at similar levels in control MoDC, whereas in MDS MoDC the pattern was heterogeneous with predominant activation of ERK over p38K. Conclusion: Our results provide strong evidence that defective signaling through NF-κB and MAPK underlies the functional abnormalities of MoDC in patients with MDS.